Dietary saturated fatty acids and prostate cancer: insights into NF-κB pathway and lipid metabolism mechanisms - Jia Wei He; Zi Xuan Huang; Yan Feng Su; Yang Qi Mo (Discover Oncology)
Abstract Prostate cancer (PCa) is one of the most prevalent malignancies in men, with dietary factors, particularly saturated fatty acids (SFAs), emerging as significant contributors to its pathogenesis. This review synthesizes current literature linking dietary fat intake, especially from dairy products, to increased prostate cancer risk, highlighting specific SFAs such as myristic and palmitic acids. The nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway is identified as a critical mediator in this relationship, promoting cell survival and proliferation in the tumor microenvironment. Additionally, the role of the lipogenic enzyme ELOVL7 is explored, emphasizing its involvement in fatty acid metabolism and cancer progression. While epidemiological and mechanistic studies provide compelling evidence for the link between dietary SFAs and prostate cancer through NF-κB activation, significant knowledge gaps remain, necessitating further research to elucidate the underlying mechanisms and potential therapeutic strategies targeting lipid metabolism.